First-aid and Concussion Knowledge of Rugby League Team Management, Administrators and Officials in New Zealand - King, D; Hume, P; Clark, T (Sports Medicine New Zealand, 2010)
Objective: To assess rugby league team management, administrators and officials’ knowledge of first-aid, concussion recognition and management and injury prevention. Methods: A descriptive study was conducted using a first-aid and concussion knowledge questionnaire consisting of two parts: (1) Thirty six multi-choice questions on first-aid assessment and knowledge incorporating five constructs (injury prevention, identification and management, cardiopulmonary resuscitation, and wound care) and, (2) Thirty eight closed- and open-ended questions on concussion recognition, management and prevention knowledge. Results: Ninety five people from the Wellington district rugby league community completed the questionnaire. Fifty two (55%) of respondents had a current up-to-date first-aid certificate which included cardiopulmonary resuscitation. Only two (2%) participants achieved the 80% passing score in the first-aid and concussion knowledge questionnaire. The mean ±SD percentages for the first-aid knowledge questions was 56 ±13% and for the 16 symptom recognition of concussion questions was 33 ±14%. Overall sports-related concussion knowledge was low (42 ±20%). Loss of consciousness was reported to be incorrectly required for a concussion to have occurred by 39% of respondents. Nearly half the respondents identified that all concussions recover at the same rate. All referees had a refereeing qualification while only 24% of coaches, 7% of managers and 2% of trainer/medics had a rugby league specific qualification. Conclusion: The first-aid and concussion knowledge results highlighted a lower understanding of sports-related first-aid and concussion than previously reported. Injury prevention and care programs in rugby league at the amateur level in New Zealand should stress first-aid and concussion injury knowledge management to enable knowledge empowerment.